Epigenetic drug combination induces remission in mouse xenograft models of pediatric acute myeloid leukemia. (July 2017) - Gopalakrishnapillai, Anilkumar; Kolb, E. Anders; McCahan, Suzanne M.; Barwe, Sonali P.
Highlights: Epigenetic drugs azacitidine and panobinostat synergistically induce AML cell death. This combination prolonged survival in disseminated mouse models of pediatric AML. Azacitidine panobinostat combination cured mice transplanted with MV4;11 cells. P53 may be a predictor of response to epigenetic therapy in pediatric AML. Abstract: Aberrations in epigenetic modifications contribute to leukemogenesis in childhood acute myeloid leukemia (AML). We combined DNA hypomethylating agent azacitidine with histone deacetylase inhibitor panobinostat in preclinical models of childhood AML. Synergistic cytotoxic effect upon treatment with azacitidine and panobinostat with combination indices <1.0 was observed. Azacitidine and panobinostat increased median survival by 26 and 6 days respectively in MV4;11 xenografted mice. Mice treated with both drugs showed a drastic reduction in leukemic burden leading to complete remission sustained for the duration of the experimental period lasting more than 519 days. Reduced leukemic burden and prolonged survival was also observed in AML-193 xenografted mice treated with azacitidine-panobinostat combination. Differential gene expression profiling was performed on AML cells treated with azacitidine, panobinostat or azacitidine-panobinostat combination. Functional mapping of transcripts uniquely regulated by the azacitidine-panobinostat combination in MV4;11 cells identified p53 as an upstream regulator. A comparison of the uniquely modulated transcripts by azacitidine-panobinostat combination in MV4;11 cells versus AML-193 and THP-1 cells, bearing mutated p53, also revealed p53 as the topmost upstream regulator. Finally, expression of mutant p53 in MV4;11 cells reduced sensitivity to azacitidine-panobinostat combination, suggesting that p53 may be a predictor of response to epigenetic therapy in pediatric AML.